Sudden death following periorbital pellet injury - Tokdemir, Mehmet; Tuerkcueoglu, Peykan; Kafadar, Hueseyin; Tuerkoglu, Abdurrahim (Taylor & Francis Ltd, 2007)
Purpose: To report an uneventful sudden death because of a periorbital pellet injury. Method: Review of autopsy findings. Results: A 20-year-old hunter was shot accidentally during hunting. At autopsy, the body showed no significant injuries or deformity except for the pellet injuries and ecchymosis on the medial side of the left lower eyelid. Skull roentgenography located a pellet in the base of the cranium. Upon craniotomy, the cause of death was diagnosed as subarachnoidal haemorrhage due to incomplete basilar artery injury. The pellet entered through the medial cantus, passed through the inferior orbital fissure than the sphenooccipital junction and basilar artery and lodged in the pons. Conclusion: A-high index of suspicion is required in order to detect an intracranial extension in periorbital injuries.
Keywords: pellet injury; transorbital; intracranial; basilar artery